CAMEL DAN TINGKAT KESEHATAN PERBANKAN - Haryanto, Melinda; Hanna, Hanna (Jurnal Akuntansi, 2014)
Abstract: This study aimed to show whether the ratio of CAMEL (Capital, AssetQuality, Management, Earnings and Liquidity) can be used as an indicator in predictingÃ‚Â the health of banks in the future. This study was carried out on the banks listed on theÃ‚Â Indonesia Stock Exchange in the period 2008-2012. Descriptive analysis and logisticÃ‚Â regression analysis are used to analyze the data. Hypothesis testing is done with theÃ‚Â normality test, Independent Sample T-Test and Mann Whitney test are used toÃ‚Â determine if two sets of data are significantly different from each other. The result ofÃ‚Â this research showed that LDR and NIM variables of bank financial conditionhave noÃ‚Â significant differents while CAR, ATTM, APB, NPL, P_PPAP, BOPO, ROA, and ROE have a significant differents. Hyphothesis testing result found that CAR, ATTM, APB, NPL, NIM, and LDR variables did not affected bank financial condition significantlyÃ‚Â while P_PPAP, ROA, ROE, and BOPO variables affected bank financial conditionsignificantly.Ã‚Â